An Information-Based Approach for Mediation Analysis on High-Dimensional Metagenomic Data - Carter, Kyle M.; Lu, Meng; Jiang, Hongmei; An, Lingling (Frontiers in Genetics, 2020)
The human microbiome plays a significant role in the development of gut-related illnesses such as inflammatory bowel disease and clinical pouchitis. A mediation model can be used to describe this interaction and may provide insight to investigate disease mechanisms. Current mediation regression methodology cannot adequately work with high-dimensional exposures and mediators or mixed data types. In particular, regression methods have a lack of power due to the non-Gaussian distribution and potentially non-linear relationship structure when the microbial species are treated as mediators. We propose two novel nonparametric procedures utilizing information theory to detect significant mediation effects with high-dimensional exposures and mediators and varying data types. Compared with available methods through comprehensive simulation studies, the proposed method has higher power and lower error. The innovative method is applied to clinical pouchitis data as well and the results are interesting.